Flexibility Matters: Impact Assessment of Small and Medium Enterprises Flexibility on the German Energy Transition - Liebensteiner, Mario; Abuzayed, Anas Ishtaiwi Salman; Hartmann, Niklas (Energy Conversion and Management: X, 2025)
This study analyzes the transition of the German electricity system towards climate neutrality by 2045, considering the demand-flexibility from small and medium enterprises (SME). The research uncovers the potential of flexibility from often-overlooked industrial SME sector, challenging their historical neglect in energy models and national strategies. Despite representing only a small fraction of peak load, SME flexibility contributes to a significant reduction in carbon emissions and transition costs, as well as a decreased reliance on other flexibility measures. However, careful design and incentivization strategies are vital to reap the full benefits of SME flexibility. Challenges in achieving a secure electricity supply during extreme weather conditions in a 100% renewable system are identified, along with how SME flexibility helps to achieve climate neutrality. By 2045, wind power becomes vital for supply security and is operated as a dispatchable ramping-up technology. Storage flexibility becomes essential. The transition incurs substantial costs but is economically advantageous in the long run. Overcapacities from renewables allow for a higher degree of electrification, stronger sector coupling, and suggest the possibility of a local hydrogen production. Although our study examines the flexibility of German SME, demand-responsive technologies exist worldwide, however with different shares and potentials. The study provides valuable insights into how SME demand response can contribute to achieving a sustainable energy system.

High electricity price despite expansion in renewables: How market trends shape Germany's power market in the coming years - Liebensteiner, Mario; Abuzayed, Anas Ishtaiwi Salman; Ocker, Fabian (Energy Policy, 2025)
Expectations about future energy prices are crucial for investment decisions, market reform debates, and public policy. Yet, the recent energy crisis caused dramatic market uncertainty. This study investigates Germany's near-future wholesale electricity price in the context of evolving market trends. A flexible econometric model is applied to high-frequency, near-time data, spanning January 2015 through May 2023. A potential endogeneity bias of trade is circumvented by an instrumental-variables approach. Results indicate that expanding renewable energy exerts downward pressure on price, countering trends like the nuclear phaseout, a rising carbon price, increased electrification, and a high gas price. The collective impact suggests a considerably higher electricity price in the coming years compared to pre-crisis levels. This finding is corroborated by a fundamental energy system model. The potential rise in renewables' production volatility may amplify electricity price volatility. A high and volatile near-future electricity price could spur investments in renewables and flexibility technologies but pose challenges for consumers. Our analysis aids evidence-based decision-making amid the post-crisis landscap
Keywords: electricity price; market trends; price prediction; renewable energy

Hydrogen-Ready Power Plants: Optimizing Pathways to a Decarbonized Energy System in Germany - Abuzayed, Anas Ishtaiwi Salman; Liebensteiner, Mario; Hartmann, Niklas (Applied Energy, 2025)

Renewable Energy Challenges and Market Dynamics in a Renewables Dominated Power System: The Case of the German Power System - Abuzayed, Anas Ishtaiwi Salman; Liebensteiner, Mario; Hartmann, Niklas (2024 20th International Conference on the European Energy Market (EEM), 2024)
The massive addition of renewables poses various challenges to system operators. The success of the German energy transition relies heavily on the availability of flexibility in the energy system. This paper investigates the market challenges and opportunities of achieving climate neutrality by 2045 in Germany. The analysis shows that in the absence of adequate incentives for storage systems, investments in gas power plants as a bridging technology may be necessary to ensure a secure supply. However, the long-term feasibility of these plants, especially post 2045 is questionable and could lead to underinvestment. Overcapacities from solar affect the utilization of other renewables. Despite renewables solely covering the demand for nearly 4500 hours, they will not be enough to achieve system security. The significance of storage flexibility becomes pronounced. However, they only experience high deployment after 2035. The insights of this work are crucial for sustainable energy planning and market design.
CRIS-Team Scopus Importer:2024-09-06
Keywords: energy system flexibility; energy transition; market dynamics; policy interventions; renewable energy challenges